2012
DOI: 10.1007/s00405-012-1950-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cochlear implantation on the vestibular function

Abstract: The aim of the present study was to examine the influence of cochlear implantation on vestibular function. The function of the horizontal semicircular canal, the saccular function, and the incidence of vestibular symptoms were assessed before and after cochlear implantation. Twenty unilaterally cochlear implant patients were evaluated preoperatively, 1 and 6 months postoperatively, with caloric testing with electronystagmography (ENG) recordings and vestibular evoked myogenic potentials (VEMP) testing. A medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 28 publications
6
57
0
1
Order By: Relevance
“…While Katsiari et al [2013] reported that the preservation rate of a normal caloric response was 51.7% (8/14) at 6 months postoperatively , all subjects with a preoperative normal caloric response also showed a normal response at 6 months postoperatively in this current study. The preoperative caloric response was aggravated 1 and 3 months after surgery and improved at 6 months in 5 subjects (subjects 5, 9, 13, 14, and 15), so the caloric response may often be conserved.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…While Katsiari et al [2013] reported that the preservation rate of a normal caloric response was 51.7% (8/14) at 6 months postoperatively , all subjects with a preoperative normal caloric response also showed a normal response at 6 months postoperatively in this current study. The preoperative caloric response was aggravated 1 and 3 months after surgery and improved at 6 months in 5 subjects (subjects 5, 9, 13, 14, and 15), so the caloric response may often be conserved.…”
Section: Discussionmentioning
confidence: 60%
“…There have been several studies about the steroid effect on HP after CI [Causon et al, 2015;Chang et al, 2009;Rajan et al, 2012], which was universally recognized. In case of vestibular preservation by steroid application, a change of vestibular function after CI was reported in several studies [Filipo et al, 2006;Katsiari et al, 2013;Meli et al, in press;Robard et al, 2015] but the evidence and the accurate mechanism of preservation effect were still not corroborated. Further research has been ongoing about several issues: the type of steroid, the method of use, timing of application, and the extent of inner ear penetration [Chandrasekhar, 2001;Chang et al, 2009;Mikulec et al, 2009;Rajan et al, 2012;Salt, 2010;Salt et al, 2011;Zou et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological studies on temporal bones implanted have shown that cochlear implantation can damage the vestibular end organ. In summary, it is clear that electrical stimulation affect vestibular system function [10] [11].…”
Section: Resultsmentioning
confidence: 98%
“…Jin et al [18,19] also reported that when the CI was activated, responses were received from patients who had previously lost the response post-operatively. On the other hand, Katsiari et al [11] stated exactly the opposite, reporting that the preoperative response observed in the CS was lost after activating the device in the postoperative period. Since, only the 500-Hz stimulus was used in these previous evaluations, it was assumed that the implant-mediated stimulation was in the apical turn [20][21][22] .…”
Section: Discussionmentioning
confidence: 98%
“…In the evaluation of saccular function after CI, only 500-Hz TB stimuli are used, and a wide range of cVEMP abnormalities have been reported [9][10][11][12] . It has been reported that cVEMP responses were not obtained, at a rate of 19%-62%, among patients with severe sensorineural hearing loss because of the anatomic and phylogenetic relationship of the cochlea with the vestibular organs, particularly the saccule; therefore, the extent of cVEMP responses and how CIs affect them remain unclear [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%